2007
DOI: 10.1021/jp068453z
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Assisted Assembly of a Heme Protein for Enhancement of Long-Range Interfacial Electron Transfer

Abstract: Interfacial electron transfer (ET) of biological macromolecules such as metalloproteins is the key process in bioelectrochemistry, enzymatic electrocatalysis, artificial ET chains, single-molecule electronic amplification and rectification, and other phenomena associated with the area of bioelectronics. A key challenge in molecular bioelectronics is to improve the efficiency of long-range charge transfer. The present work shows that this can be achieved by nanoparticle (NP) assisted assembly of cytochrome c (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
147
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 57 publications
4
147
0
Order By: Relevance
“…Reversible interfacial ET was observed, and the ET rate was estimated as 25 s À 1 by the Laviron method (Supplementary Fig. S3) 32,33 . The surface population of terpy, estimated from the reductive desorption ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reversible interfacial ET was observed, and the ET rate was estimated as 25 s À 1 by the Laviron method (Supplementary Fig. S3) 32,33 . The surface population of terpy, estimated from the reductive desorption ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, when biomolecules are conjugated with nanoparticles, the mixing of their energy levels has been shown to favour the occurrence of either energy transfer or electron transfer phenomena [7,8]. In this way, it is possible to study fundamental processes characterizing the interaction of metal nanoparticles with organic or biological molecules [4,9,10]. Furthermore, nanoparticle properties can be exploited for realizing nanohybrid systems for various applications, also thanks to the possibility to suitably design their characteristics with a proper selection of the employed biotic element [3,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the analysis of the overall characteristics of the plasmon band can be exploited to elucidate phenomena occurring at nanoparticle interface, including bioconjugation and molecular recognition [10,36]. Accordingly, three factors can be invoked as possible causes of the plasmon band shift and/or broadening detected in the absorption spectra of Az+AuNP solutions: (a) aggregation of nanoparticles upon bioconjugation, (b) electronic communication between the Az redox center and the gold nanoparticle, and (c) changes in local dielectric environments.…”
mentioning
confidence: 99%
“…Kolb et al modified the Au (111) electrode with Zn, Fe and Cu nanoclusters by electron probe [15,16], however, the method is far from universal since it needs strict control and complicated operation, the area of electrode being modified is greatly limited so the efficiency is low. In recent years, assembling the surface functional NPs onto electrode was commonly used to form modified electrode [17,18]. Generally, in this method, ligands with strong affinity to Au (such as thiol) was adopted to react with weak ligands (such as citrate [19] and phenylphenol [20]) protected Au NPs, forming functional Au NPs, and then the functional NPs were adsorbed onto the electrode surface to form NPs modified electrode.…”
Section: Introductionsmentioning
confidence: 99%